Sustainability of Malay wood craftsmanship symbolism in deciphering Malaysia’s architectural identity - Azmin, Aida Kesuma; Abdullah, Fadzidah; Sanusi, Aliyah Nur Zafirah; Yusof, Zeenat Begam; Asif, Nayeem (2021)
Traditional Malay architecture symbolizes the manifestation of Malaysia’s indigenous cultural heritage throughout centuries. Unfortunately, many elements of the architecture are depleting fast, due to improper maintenance, and the demise of Malay woodcarver artisans. Studies have shown that the issue of nonexistence of cultural meanings in contemporary housing is due to global proficiency, profit-making, and insensitivity of Western architecture compared to the traditional architecture. Worse, some developers in Malaysia claims generic wood craftsmanship in local housing designs as traditional Malay craftsmanship, which in truth do not belong to a certain region, nor portraying a reflection of the owner’s personality. Wood, as a spiritual building material in traditional Malay houses are symbolically represented by its wood carving’s artistry, which contain embedded values of principles, supremacy, hierarchy, religiousness, and versatility of its owners. Therefore, this study aims to establish the notions of Malay wood craftsmanship symbolism in deciphering traditional Malay’s architectural Identity. The craft deserves to be regenerated and adopted into the contemporary buildings in order to maintain Malaysia’s traditional architectural identity. Hence, the study’s objectives are to elucidate the variants of wood carvings’ functions in traditional Malay houses, to determine its symbolic meanings based on culture and religious influences; and identify the future challenges and opportunities for its sustainability. This study adopts qualitative methodology, such as case studies, in depth interviews, observation, and reviews of measured drawings from KALAM center, UTM. Apart from the wood carving motifs’ physical function as natural ventilator, daylighting device, structural, decorative design elements, the findings discover some symbolic and cosmological meanings, which are closely related to God’s creations such as flora and fauna; the cosmos, including the sun, moon and stars; journey to eternal life, and Islamic beliefs. The findings also identify few challenges and opportunities that include the lack of interest and knowledge, and loss of identity due to architectural globalism. There is still some opportunities to revitalize traditional Malay craftsmanship in contemporary Malaysian housing. This study will rejuvenate the forgotten Malay inheritance to be imbued in contemporary housing in Malaysia.